29. PARENTAL KNOWLEDGE OF CHILDREN UNDER 5 YEARS OLD ABOUT DISEASE AND DIPHTHERIA VACCINATION (Vietnam Journal of Community Medicine, 2024)
Objectives: To assess the percentage of children’s parents having sufficient knowledge toward disease and diphtheria vaccination in Dak Nong province in 2021.Methods: The study was performed between May to June 2021 using a descriptive cross-sectional design among parents of children under 5 years old in Dak Nong province. Data was collected via a structured questionnaire.Results: A total of 238 parents completed the survey, there is a mean age of 29 (25-33) years. 78.6% of parents had sufficient knowledge of disease and diphtheria vaccination. There was a significant relationship between knowledge and preventive practice of diphtheria (p
Keywords: Diphtheria, knowledge, immunization, children